Islamic Religious Education in the Formation of Spiritual Resilience in Drug Users: A Systematic Review of the Literature - Ibnu Chudzaifah; Sukiman; Sibawaihi; Akhmad Roja Badrus Zaman (State Islamic Institute of Madura, 2025)
This study aims to explore the role of Islamic Religious Education and spirituality in the recovery process of drug addicts. with the Systematic Literature Review (SLR) approach. Through spiritual approaches such as dhikr, prayer, meditation, and introspection, Islamic education provides emotional support, improves mental health, and strengthens the psychological resilience of addicts. Several countries such as Uzbekistan, the United States, and Malaysia have implemented a spiritual-based rehabilitation approach that has proven effective, by adapting local values. In Indonesia, the Inabah method applied in Islamic boarding schools has succeeded in helping thousands of addicts in their recovery. In addition, the use of technology such as the Virtual-Inabah application increases the accessibility and effectiveness of spiritual-based therapy. These findings suggest that the integration of religious education and Islamic psycho-spiritual approaches can improve the quality of life of addicts and reduce the risk of relapse.